2015
DOI: 10.1016/j.nicl.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Brain and cord myelin water imaging: a progressive multiple sclerosis biomarker

Abstract: ObjectivesConventional magnetic resonance imaging (MRI) is used to diagnose and monitor inflammatory disease in relapsing remitting (RR) multiple sclerosis (MS). In the less common primary progressive (PP) form of MS, in which focal inflammation is less evident, biomarkers are still needed to enable evaluation of novel therapies in clinical trials. Our objective was to characterize the association — across the brain and cervical spinal cord — between clinical disability measures in PPMS and two potential bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 52 publications
3
46
0
1
Order By: Relevance
“…VF m provides increased specificity to myelin over DTI, and is sensitive to age‐related processes in myelin in our sample. VF m 's sensitivity to myelin has been validated histologically in healthy and cuprizone‐treated mice (Wood et al, ) and the shaking pup model (Hurley et al, ), along with in vivo studies of multiple sclerosis (Kolind et al, ; Kolind et al, ), and it shows good reproducibility within and across sites (Laule & Moore, ). Previous imaging studies using the same measure have shown rapid myelination during infancy (Deoni et al, ; Deoni et al, ), and histological studies have shown continued myelination into adolescence (Benes, ; Yakovlev & Lecours, ), but this is the first study to demonstrate VF m trends in late childhood and adolescence, and the first to show ongoing myelination in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VF m provides increased specificity to myelin over DTI, and is sensitive to age‐related processes in myelin in our sample. VF m 's sensitivity to myelin has been validated histologically in healthy and cuprizone‐treated mice (Wood et al, ) and the shaking pup model (Hurley et al, ), along with in vivo studies of multiple sclerosis (Kolind et al, ; Kolind et al, ), and it shows good reproducibility within and across sites (Laule & Moore, ). Previous imaging studies using the same measure have shown rapid myelination during infancy (Deoni et al, ; Deoni et al, ), and histological studies have shown continued myelination into adolescence (Benes, ; Yakovlev & Lecours, ), but this is the first study to demonstrate VF m trends in late childhood and adolescence, and the first to show ongoing myelination in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…VF m 's sensitivity to myelin has been validated histologically in healthy and cuprizone-treated mice (Wood et al, 2016) and the shaking pup model (Hurley et al, 2010), along with in vivo studies of multiple sclerosis (Kolind et al, 2012;Kolind et al, 2015), and it shows good reproducibility within and across sites (Laule & Moore, 2018). Previous imaging studies using the same measure have shown rapid myelination during infancy (Deoni et al, 2011;Deoni et al, 2012), and histological studies have shown continued myelination into adolescence (Benes, 1989;Yakovlev & Lecours, 1967) (Krogsrud et al, 2016), but further research is needed to investigate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Caution should therefore be taken when comparing in‐vivo results with formalin fixed ex‐vivo histology (Schmierer et al, ). In another study, MWF and volume of the brain and spinal cord of primary progressive MS patients and healthy controls were obtained using mcDESPOT (Kolind et al, ). Changes in brain volume (suggested to indicate atrophy) were found to correlate with cognitive processing, evaluated using Paced Auditory Serial Addition Test and dexterity, evaluated using the 9‐Hole Peg Test (9‐HPT).…”
Section: Myelin Mr Imaging Applicationsmentioning
confidence: 99%
“…Changes in brain volume (suggested to indicate atrophy) were found to correlate with cognitive processing, evaluated using Paced Auditory Serial Addition Test and dexterity, evaluated using the 9‐Hole Peg Test (9‐HPT). MWF (indicating myelin) was found to correlate with 9‐HPT performance in the corpus callosum (Kolind et al, ). The MWF and f B however, have been found to only partially correlate, indicating that one or both measures may not specifically measure myelin but could also be affected by other factors such as axonal loss or inflammation (Tozer et al, ).…”
Section: Myelin Mr Imaging Applicationsmentioning
confidence: 99%
“…Finally, mcDESPOT makes use of conventional MR acquisition sequences, namely, fully balanced steady state free precession (bSSFP) and spoiled gradient recalled echo (SPGR), widely available on clinical MRI systems. Overall, then, mcDESPOT is particularly attractive for clinical investigations (26, 30, 45). …”
Section: Introductionmentioning
confidence: 99%